PENGARUH EARNING PER SHARE (EPS), RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), DAN CURRENT RATIO (CR) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 (Students' Journal of Accounting and Banking, 2015)
This study aimed to examine the effect of Earning Per Share (EPS), Return On Asset (ROA), Return On Equity (ROE), and Current  Ratio (CR) of stock price manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population is the entire manufacturing company in Indonesia Stock Exchange (IDX) with 152 companies and research during the period of 2011-2013. Samples taken in this study is 68 companies. The sampling technique used purposive sampling. The analytical tool used in study is Multiple Linear Regression Analysis. The results showed that for the test statistic F-test, Earning Per Share (EPS), Return On Asset (ROA), Return On Equity (ROE), and Current  Ratio (CR) jointly influence on stock prices. Partial results of hypothesis testing indicates that there is a positive effect of the Earning Per Share (EPS) of the stock price. As for the Return On Asset (ROA), Return On Equity (ROE), and Current Ratio (CR) showed no effect on stock prices. Keywords: Earning Per Share, Return On Asset, Return On Equity, Current Ratio, and Stock Price